Understanding Social Cohesion from the Perspective of the Host Community: Turkey Example - Ilgar Seyidov (Journal of Economy Culture and Society)
According to recent statistics from the DGMM (Directorate General of Migration Management of Turkey), more than 3,5 million Syrian refugee people are living in Turkey. This number, however, reflects only registered Syrians, not the many unregistered Syrian refugees and asylum-seekers also living in Turkey. In order to cope with the refugee crisis, various projects are being conducted through the support of national and international funds. Social cohesion has been identified as a key to integrating host and refugee communities. Socio-cultural activities hve been designed to include participants from both communities. In this context, this study aims to discover the attitudes of Turks toward social cohesion which is promoted to be built between them and refugees. This limited research relied on a semi-structured in-depth interview technique as research methodology for a random sample of 45 residents of Ankara living in neighborhoods that contain a high number of refugees. The main reason of limiting the number of participants with 45 was related to reputation. According to findings, the members of the host community are in favor of developing social contact with refugees; however, misinformation and rumors, language barriers, and a lack of social connection were considered as the main factors affecting the negative attitudes of the host community members towards refugees.